Taxonomic and morphological characterization of genus Neolimnus Linnavuori (Hemiptera: Cicadellidae, Deltocephalinae, Phlepsiini), with description of two new species - El-Sonbati, Saad A.; Dietrich, Christopher H.; Wilson, Michael R.; Harbi, Meshari M. Al; Dhafer, Hathal M. Al (Zootaxa, 2026)
The genus Neolimnus Linnavuori, 1953 is revised and its differential diagnostic characters are given. Six species in two subgenera are reviewed. Neolimnus ageratus bicornis Heller & Linnavuori, 1968 is considered here to be a nomen nudum. A lectotype is designated for Deltocephalus ageratus Melichar, 1904. Two new species, Neolimnus eltorkeyi sp. nov. and Neolimnus jumanae sp. nov. are described. A key to subgenera and species is provided.